Unlivable lives: violence and identity in transgender activism - Westbrook, Laurel (University of California Press, 2021)
Unlivable lives : the origins and outcomes of identity-based anti-violence activism -- Violence matters : producing identity through accounts of murder -- Atypical archetypes : the causes and consequences of famous victims of violence -- Homogeneous subjecthood : how activists' focus on identity obscures patterns of violence -- Valuable and vulnerable : how activists' tactical repertoires shape subjecthood and generate fear -- Shaping solutions : how identity politics influence violence prevention efforts -- Facilitating livable lives : alternative approaches to anti-violence activism -- Methodological appendix A : transgender anti-violence organizations -- Methodological appendix B : collecting data on murders of transgender people.